Intersections of law and culture at the International Criminal Court - Fraser, Julie; McGonigle Leyh, Brianne (Edward Elgar Publishing, 2020)
Intersections of law and culture at the International Criminal Court : introduction / Julie Fraser and Brianne McGonigle Leyh -- Now you see it, now you don't : culture at the International Criminal Court / Leigh Swigart -- How to solve a problem like Al Madhi : proposal for a new crime of 'attacks against cultural heritage' / Peta-Louise Bagott -- Cultural heritage destruction and the ICC : lessons from connecting cultural heritage and human rights through a library lens / Vicky Breemen and Kelly Breemen -- Keeping the 'delicate mosaic' together : can the ICC deal with intangible cultural heritage? / Martyna Fałkowska-Clarys and Lily Martinet -- the emergence of gender justice at the ICC / Alison Dundes Renteln -- 'Solemnly declare to tell the truth' : internationalising the solemn undertaking before the International Criminal Court / Joshua Isaac Bishay -- Spellbound at the International Criminal Court : the intersection of spirituality and international criminal law / Adina-Loredana Nistor, Andrew Merrylees and Barbora Holá -- 'Questioned by the Court' : the role of judges and sociocultural aspects of testimonial evidence in Katanga / Suzanne Schot -- The power of culture and judicial decision-making at the International Criminal Court / Gregor Maučec -- Doing 'justice' at the Office of the Prosecutor : portrayals of a cultural value / Cale Davis -- In defence of culture : should defences based on culture apply at the ICC? /Noelle Higgins --Introducing aspects of transformative justice to the International Criminal Court through plea negotiation /Phoebe Oyugi and Owiso Owiso --'Culture' and sentencing at the International Criminal Court /Michelle Coleman --A delicate mosaic : the ICC, culture and victims /Fiona McKay --The quest for cultural legitimacy at the ICC : a third-way approach as an appropriate response to African cultural paradigms /Ingrid Roestenburg-Morgan --'We will let it die on its own' : culture, ideology and power at play between the United States and the International Criminal Court /Brianne McGonigle Leyh --Asia's reluctance to join the ICC : who is jilted by whom? /Nikhil Narayan --Exploring legal compatibilities and pursuing cultural legitimacy : Islamic law and the ICC /Julie Fraser --Afterword : culture, genuine and juridical /Mark Goodale.